Interaction of a universal adhesive with different surface treatments with feldespathic ceramics - Diana Alejandra Suárez-Moya; Alberto Carlos Cruz-González; Juan Norberto Calvo-Ramírez (Elsevier, 2019)
Introduction: Universal adhesives provide the possibility of simplified protocols for using ceramics; however, determining the synergy of these adhesives with silanes and the possibility of replacing silanes requires extensive research. Objective: To evaluate the influence of a universal adhesive, associated with airborne-particle abrasion, acid etching, and silane, on the bond strength of a feldspathic ceramic CAD-CAM to composite resin. Materials and methods: CAD-CAM feldspathic ceramic blocks were cut into 2-mm slices and were randomly divided into six groups (n = 10): A1, Single Bond Universal (SBU); A2, Adper Single Bond 2 (SB2); B1, silane + SBU; B2, silane + SB2; C1, acid etching + silane + SBU; C2, and acid etching + silane + SB2. Tygon tubes were placed and filled with composite resin. All samples were stored in distilled water at 37 °C for 24 h and then subjected to micro-shear tests. The type of failure was analyzed using a stereomicroscope. Results: SBU demonstrated slightly higher adhesion values compared with SB2 in all groups; however, no significant differences were observed between the adhesives (p < 0.05). Conclusion: SBU was not statistically superior to the control adhesive. The use of silane prior to a universal adhesive should not yet be eliminated. Keywords: Adhesives, Universal bond, Surface properties, Methacryloxypropyltrimethoxysilane, 10-methacryloyloxydecyl dihydrogen phosphate, Dental restoration repairs (MeSH)